Réponses

2012-09-24T22:47:26+02:00

- 2x² + 40 - 102 = 0

- 2x² - 62 = 0

x² = - 62/2

aucune solution

 

2x² - 6 x + 8 = 0

2(x² - 3x + 4) = 0

x² - 3x + 4 = 0

(x-3/2)² = x² - 3x + 9/4

(x-3/2)² + 7/4 = 0

aucune solution

 

2x² - 3 = 8x + 9

2x² - 3 - 8x - 9 = 0

2x² - 8x -12 = 0

2(x² - 4x - 6) = 0

x² - 4x - 6 = 0

(x-2)² = x² - 4x + 4

(x-2)² - 10 = 0

(x-2)² - (V10)² = 0

(x-2-V10)(x-2+V10) = 0

2 solutions : x = 2 +V10 ou x = 2-V10

 

4x = 5x² - 1

5x² - 4x - 1 = 0

5(x² - 4x/5 - 1/5) = 0

x² - 4x/5 - 1/5 = 0

(x-2/5)² = x² - 4x/5 + 4/25

(x-2/5)² - 9/25 = 0

(x-2/5)² - (3/5)² = 0

(x-2/5 - 3/5)(x-2/5 + 3/5)

(x - 1)(x + 1/5)

2 solutions : x = 1 ou x = -1/5

 

en espérant t'avoir aidé.